Risking Your Health : Causes, Consequences, and Interventions to Prevent Risky Behaviors - de Walque, Damien (Washington, DC: World Bank, 2013)
Behaviors that pose risks for an individual’s health and that also represent important threats for public health, such as drug use, smoking, alcohol, unhealthy eating causing obesity, and unsafe sex, are highly prevalent in low income countries, even though they are traditionally associated with richer countries.